MAKING DEVICES USING AT89C51 MICROCONTROLLER WITH CASE STUDY IN SPEAKER FOR AND 750HZ 500HZ FREQUENCY GENERATED - Jimmi Parulian Hutapea; Indrianto Indrianto, SKom, MT (Jurnal Sistem Informasi, 2005)
The development of computer technology is rapidly evolving, making all activitieseasier and more effective. As a result, office work, service and entertainmenttechnology depends on the same computer.Microcontroller technology is the result of the development of computer technologyand microcontroller which will produce a sophisticated, making application simplebecause the program will be in the program in the IC, in this case the IC AT89C51.In this case, the authors make a design tool which will be generated frequency 500Hzand 750 Hz alternately using asembler programming language.